Comparison of essential medicines lists in 137 countries. - Persaud, N; Jiang, M; Shaikh, R; Bali, A; Oronsaye, E; Woods, H; Drozdzal, G; Rajakulasingam, Y; Maraj, D; Wadhawan, S; Umali, N; Wang, R; et al. (World Health Organisation, 2019)
Objective:To compare the medicines included in national essential medicines lists with the World Health Organization's (WHO's) Model list of essential medicines, and assess the extent to which countries' characteristics, such as WHO region, size and health care expenditure, account for the differences. Methods:We searched the WHO's Essential Medicines and Health Products Information Portal for national essential medicines lists. We compared each national list of essential medicines with both the 2017 WHO model list and other national lists. We used linear regression to determine whether differences were dependent on WHO Region, population size, life expectancy, infant mortality, gross domestic product and health-care expenditure. Findings:We identified 137 national lists of essential medicines that collectively included 2068 unique medicines. Each national list contained between 44 and 983 medicines (median 310: interquartile range, IQR: 269 to 422). The number of differences between each country's essential medicines list and WHO's model list ranged from 93 to 815 (median: 296; IQR: 265 to 381). Linear regression showed that only WHO region and health-care expenditure were significantly associated with the number of differences (adjusted R2 : 0.33; P < 0.05). Most medicines (1248; 60%) were listed by no more than 10% (14) of countries. Conclusion:The substantial differences between national lists of essential medicines are only partly explained by differences in country characteristics and thus may not be related to different priority needs. This information helps to identify opportunities to improve essential medicines lists.